1647. Real-Time Metagenomic Sequencing Reveals Discrete Transmission Clusters Within a Hospital-Associated Norovirus Outbreak. (26th November 2018) - Casto, Amanda; Adler, Amanda; Makhsous, Negar; Qin, Xuan; Crawford, Kristen; Jerome, Keith; Zerr, Danielle; Greninger, Alex
Abstract: Background: Norovirus is the most common cause of acute gastroenteritis in the United States and a major challenge for infection control efforts. The high burden of norovirus in most communities and health care systems makes it difficult to discern viral transmission patterns using traditional epidemiological approaches alone. Methods: We performed real-time metagenomic sequencing of norovirus isolates from an outbreak among inpatients at Seattle Children's Hospital (SCH). We also sequenced isolates from norovirus cases within the larger University of Washington (UW) Medical System that occurred during and after the outbreak. Results: Our data showed that the month-long outbreak at SCH was actually characterized by 3 distinct concurrent transmission clusters contained within 3 different hospital units. We were able to report this information to the infection control team at SCH while the outbreak was still in progress. The virus responsible for one of these 3 clusters was genetically stable over a period of 4.5 weeks suggesting serial transmissions from a contaminated fomite, rather than patient to patient transmission. After cases meeting the epidemiological definition for hospital-acquired had ceased, we demonstrated that the virus from one of the 3 outbreak clusters continued to be transmitted to other patients within the SCH medical system. Finally, we showed that one of the patients who acquired norovirus during the outbreak developed a chronic infection with viral shedding documented up until the time of the patient's death, 8 months after the outbreak. Conclusion: These results demonstrate the value of using metagenomics as an adjunct to traditional epidemiologic techniques in the setting of a hospital-associated norovirus outbreak. Real-time metagenomic sequencing elucidated viral transmission patterns within the outbreak while it was still in progress and follow-up sequencing revealed further infections due to an outbreak-associated viral strain even after the outbreak was thought to be over. Given this potential, metagenomic analyses represent an invaluable, largely untapped resource for improving our understanding of and reducing adverse effects from viral outbreaks. Disclosures: All authors: No reported disclosures.